Retraction Note to "Environmental and Economic Impact of Employing Solar Chimney and Photovoltaic Cells in Buildings with Various Climates" [Advanced Energy Conversion Materials, Volume 2 Issue 2 (2021), 45-49] - Universal Wiser Publisher (Advanced Energy Conversion Materials, 2025)
The Editor-in-Chief and the Editorial Office of Advanced Energy Conversion Materials (AECM) have retracted the following article: Jahangir MH, Nateghi SK. Environmental and Economic Impact of Employing Solar Chimney and Photovoltaic Cells in Buildings with Various Climates. Advanced Energy Conversion Materials. 2021; 2(2): 45-59. This article has been retracted at the request of the Editor-in-Chief. Following a journal-wide investigation, it was identified that this article falls outside the scope of the journal and no issues with data integrity or research ethics, and does not align with the thematic focus or subject matter requirements as outlined by the journal’s editorial policies. The retraction is in accordance with the Committee on Publication Ethics (COPE) guidelines, ensuring the integrity of the publication record is maintained. As part of journal’s ongoing efforts to improve the quality of publications, the editorial office will continue to rigorously conduct preliminary review and peer review to ensure that only manuscripts that align with the journal’s scope and meet the highest academic standards are published. The editorial office sincerely apologize for any confusion or inconvenience this retraction may have caused.